Competence of Arbitration and National Courts to Apply Arbitral Interim Measures - Machaidze, Otar (Alternative Dispute Resolution Yearbook, 2019)
The paper discusses one of the crucial institutes of arbitration proceedings - interim measures and related thereto aspects. Subject to analysis is the competence of arbitral tribunal and court of law in ordering interim measures in arbitration and the grounds for restriction of their powers. The paper also offers the review of the evolution of the institute of interim measure and modern international trends. Particular attention is paid to the analysis of the efficiency of interim measures applied by court of law and arbitral tribunal.